2014
DOI: 10.1155/2014/583730
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Scar Formation on Application of Terpenoid Fraction of Tuberous Root ofMirabilis jalapaL. on Excision Wound Model in Wistar Albino Rats

Abstract: The study was designed to evaluate the effects of hydromethanolic extract of tuberous root of M. jalapa and its terpenoid and flavonoid fractions on cutaneous wound healing in Wistar Albino rats. The hydromethanolic extract was subfractionated by sequential extraction in solvents (moderately nonpolar to polar). The extract and its (terpenoid and flavonoid) fractions were used for cutaneous wound healing studies by using excision wound model on rat. Their effects on wound contraction rate, biochemical and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The authors concluded that terpenoid fractions prolonged the proliferation phase and had a tendency to convert the wound into a hypertrophic wound [114].…”
Section: Dermatological Effectmentioning
confidence: 99%
“…The authors concluded that terpenoid fractions prolonged the proliferation phase and had a tendency to convert the wound into a hypertrophic wound [114].…”
Section: Dermatological Effectmentioning
confidence: 99%
“…The results indicated that flavonoid caused significant decrease (P<0.05) in antioxidant enzyme level as compared to control in wound healing process, whereas terpenoid fraction caused significant increase (P<0.05) in expression of growth factor levels but regeneration and remodeling stages were delayed due to formation of thicker ulcus layer and also there were no hair follicle-like blood capillaries formation which ultimately may lead to formation of hypertrophic scar of wound. The authors concluded that terpenoid fraction prolonged proliferation phase and have tendency to convert the wound into hypertrophic wound [60].…”
Section: Dermatological Effectmentioning
confidence: 99%